The importance of electron transfer in determining properties of [NiFe]-hydrogenases - Murphy, B (2013)
[NiFe] hydrogenases are microbial metalloenzymes that catalyse the reversible interconversion between molecular hydrogen and protons with high selectivity and efficiency. The catalytic properties of different [NiFe] hydrogenases vary according to the physiological roles they each play, yet all seem to be based upon an almost identical catalytic site architecture. Through efforts to understand the structural and mechanistic basis for the differing properties of [NiFe] hydrogenases, it has become increasingly evident that electron transfer to and from the active site, mediated by a set of Iron-Sulphur clusters, influences to a significant extent the observed catalytic properties of different hydrogenases. Here we present a comprehensive study of E. coli Hyd-1, an O2-tolerant hydrogenase, by PFE with a focus on the properties that are characteristic of O2-tolerant enzymes: overpotential requirement, lack of H2 production, low KH2M, and high Eswitch. We show that Hyd-1 catalysis can be made reversible by increasing the equilibrium potential for the reaction through changes in substrate concentration, and that electron transfer into and out of the enzyme molecule, rather than active site properties, is responsible for the characteristics of overpotential and bias in Hyd-1. We present a set of experiments with Hyd-2 from E. coli in which surface-exposed cysteine residues are specifically introduced near the distal and medial Iron-Sulphur clusters to act as points of attachment for photosensitizer molecules, and a study of the kinetics of electron injection from photoexcited molecules to the enzyme and subsequent absorbance changes attributed to transient redox changes at the active site. We are able to show lightdependent H2 production from a Hyd-2 + photosensitizer system. Finally, we present the first purification of the formate-hydrogen lyase (FHL) complex from E. coli, the complex responsible for H2-production by this organism during fermentation, and we provide a characterisation of the complex by EPR and PFE. The properties of Hyd-3, the hydrogenase subunit of the FHL, seem to differ from those observed previously for other [NiFe] hydrogenases.